Neo-Carbon Energy World - What Opportunities for Chile?: Neo-Carbon Energy Futures Clinique IV - Sirkka Heinonen; Noora Vähäkari; Joni Karjalainen (Turun yliopisto, Tulevaisuuden tutkimuskeskus, 2025)
This report presents the results of the “Neo-Carbon Energy World – What Opportunities for Chile?”, a futures clinique organised at the Chilean Intellectual Property Institute INAPI in Santiago de Chile 24th October 2016, jointly by Finland Futures Research Centre of the University of Turku and Consejo Chileno Prospectiva y Estrategia (CChPE). Chile is a case study conducted in the foresight part of the Neo-Carbon Energy project. Chile is a country with robust renewable energy resources, which has received high attention by international investors and has led to a dramatic increase in the uptake of solar energy in the country. Chile is also a pioneer in economic development in Latin America, thanks to its steady political and economic conditions. The country keeps on investing in education to catalyze socio-economic development, but remains underpinned by the deepest inequalities in OECD countries. In the Futures Clinique, four transformative scenarios of 2050 of the Neo-Carbon Energy research project were used to analyse the relevance and opportunities of the energy transformation with renewable energy technologies in Chile. In the group work, each group worked on one of the four scenarios (Radical Start-ups, Techemots, Do-It-Yourself Green Engineers, New Consciousness) to reflect the significance of this scenario to Chile. The participants of the Radical Startups group emphasized that the startup culture and enabling political focus have not taken up yet. No matter the nature and scale of an organization, they should put more effort in citizen wellbeing and societal needs. Those analyzing the Value-Driven Techemoths scenario found that at the moment, there are few Chilean technology companies. However, there are large enterprises in the country, in the hands of a few powerful families. A trajectory where their position strengthens would not automatically be beneficial to the society, unless these companies genuinely commit to commonly shared values of environmental protection, climate change mitigation, and social wellbeing. The Green DIY Engineers group found that their scenario was unfit as such for the Chilean context. Individual households were deemed as too small units and instead small towns and communities were seen as more suitable sized units for the do-it-yourself context. If these towns would have low hierarchies and that authorities that act based on local needs, such a model would be equitable and provide sustainable development for the country. According to the New Consciousness group, values would have to change considerably and citizendriven change would have be re-established. As a profound, cross-cutting aim that drives the nation, deep ecological New Consciousness would be supported with open governance and new institutions of horizontal governance ensure the uptake of renewable energy and quality of life extremely locally. As a conclusion, energy is a complex phenomenon, and a revolutionary transformation of a sector as broad brings up its complex nature that touches upon social, economic, cultural and environmental values and norms. Economic diversification in a resource-dependent economy such as Chile requires 6 restructuring of the system. Simultaneously, decentralized energy production, such as the Neo-Carbon Energy project suggests, urges courage and trust, something that Chileans claim they often miss. Peerto-peer mentality might be more difficult to adapt than ecological consciousness, as the political history, socio-economic inequality and culture constantly challenge trust and credibility. Government and public organizations that are distant to the needs and hopes of citizens are awarded with skepticism. If the country wants to be a pioneer of the renewable energy industry in Latin America, it should also question the ownership of the projects and investments as they are now, since all of them are currently foreign. For further research, we are looking more deeply into the transformation of the renewable energy sector and the discussion as of now. It is also necessary to understand any previous social change processes in Chile and see whether the abovementioned features are evident there too. The question of national ownership of the process is similarly interesting. The Clinique process and scenarios need to be reviewed critically particularly when bringing into a new socio-cultural or economic context. The analysis phase needs to specified and determined better to avoid subjective perceptions. However, this exercise showcased well the loopholes and strengths of the method in a foreign context, and brought new perspective of thinking about the future to tens of energy sector experts in Chile with rather little experience on participative and innovative working processes.